The widespread impacts of remittance flows - Catalina Amuedo Dorantes; Susan Pozo (IZA World of Labor, 2023)
Remittances have risen spectacularly in absolute terms and in relation to traditional sources of foreign exchange, such as export revenues. Remittances can improve the well-being of family members left behind and boost growth rates of receiving economies. They can also create a culture of dependency, lowering labor force participation in recipient nations, promoting conspicuous consumption, and accelerating environmental degradation. A more thorough understanding of their impacts can help formulate policies that enable developing economies to harness the most out of these monetary inflows.
Keywords: F24; O1; O2; 330; remittances; consumption smoothing; remittance policy; developing economies